Factors associated with HIV testing and treatment among young Black MSM and trans women in three jail systems. Issue 1 (2nd January 2023) - Antos, Nicholas; Flores, Rey; Harawa, Nina; Vecchio, Natascha Del; Issema, Rodal; Fujimoto, Kayo; Khanna, Aditya S.; Paola, Angela Di; Schneider, John A.; Hotton, Anna L.
ABSTRACT: Black men who have sex with men (BMSM) and transgender women (BTW) are disproportionately affected by incarceration and HIV. We assessed factors associated with HIV testing and viral suppression among 176 incarcerated BMSM and BTW in Chicago, IL; Los Angeles, CA; and Houston, TX. In multivariable logistic regression, having a sexual orientation of bisexual, heterosexual, or other vs. gay or same-gender loving was associated with higher odds of testing in custody (aOR 8.97; 95% CI 1.95 - 41.24). Binge drinking (aOR 0.19; 95% CI 0.04 - 0.92) and being unemployed prior to incarceration (aOR 0.03; 95% CI 0.00 - 0.23) were associated with lower odds of testing; participants in Los Angeles were also more likely to be tested than those in Chicago. Being housed in protective custody (aOR 3.12; 95% CI 1.09-9.59) and having a prescription for ART prior to incarceration (aOR 2.58; 95% CI 1.01-6.73) were associated with higher odds of viral suppression when adjusted for site and duration of incarceration, though the associations were not statistically significant in the full multivariable model. Future research should examine structural and process level factors that impact engagement in HIV testing and treatment among detained BMSM and BTW.